2005
DOI: 10.1007/11496618_7
|View full text |Cite
|
Sign up to set email alerts
|

All in the XL Family: Theory and Practice

Abstract: Abstract. The XL (eXtended Linearization) equation-solving algorithm belongs to the same extended family as the advanced Gröbner Bases methods F4/F5. XL and its relatives may be used as direct attacks against multivariate Public-Key Cryptosystems and as final stages for many "algebraic cryptanalysis" used today. We analyze the applicability and performance of XL and its relatives, particularly for generic systems of equations over medium-sized finite fields.In examining the extended family of Gröbner Bases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 40 publications
1
43
0
Order By: Relevance
“…4 becomes non-positive. This is the meaning of "no extraneous dependencies" in [28,40], and semi-regularity in [2]: the XL-equations constructed according to an extension of the Buchberger criteria ( [19]) have no extraneous interdependencies. Bardet et al (nor anyone else) give no general properties implying semi-regularity.…”
Section: Basic Combinatorial Results Concerning XLmentioning
confidence: 99%
See 3 more Smart Citations
“…4 becomes non-positive. This is the meaning of "no extraneous dependencies" in [28,40], and semi-regularity in [2]: the XL-equations constructed according to an extension of the Buchberger criteria ( [19]) have no extraneous interdependencies. Bardet et al (nor anyone else) give no general properties implying semi-regularity.…”
Section: Basic Combinatorial Results Concerning XLmentioning
confidence: 99%
“…[3,27,35,40]). If the system matrix can be blocked efficiently via coloring analysis ( [16]), only the dominant block counts for T and R. When m, n → ∞ so does R/T .…”
Section: A Framework For Estimating Security Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…[3] for an overview of the idea. Although it has been shown that techniques from the XL-family are strictly less efficient than from the F-family [40,39,5,17], XL does have its merits as it is easier to adapt to different settings. Hence we have used a specialized version of XL in our solver to improve its efficiency, cf.…”
Section: Related Workmentioning
confidence: 99%